2023
DOI: 10.11591/ijere.v12i1.23632
|View full text |Cite
|
Sign up to set email alerts
|

Hoax behavior tendencies among Indonesian students: An analysis during the COVID-19 pandemic

Abstract: <span lang="EN-US">The objective of this study was to analyze the hoax behavior tendencies among Indonesian students during the pandemic, viewed from the aspects of analytical thinking, basic science knowledge, trust in news sources, satisfaction, and action. A total of 633 male and female students from Indonesian universities were sampled used a simple random sampling technique. Data were collected through the hoax tendency behavior scale (HTBS) on 30 questions using a Likert scale. Then, the data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The results of this study indicate that adolescent selfconfidence has a positive effect on their self-efficacy in making decisions regarding their future careers. Based on investigations conducted by Ireland and Lent [7], Brown and Lent [6] and Life et al [11], the findings contribute to a deeper understanding of SCCT [6], [11]- [15].…”
Section: Introductionmentioning
confidence: 72%
“…The results of this study indicate that adolescent selfconfidence has a positive effect on their self-efficacy in making decisions regarding their future careers. Based on investigations conducted by Ireland and Lent [7], Brown and Lent [6] and Life et al [11], the findings contribute to a deeper understanding of SCCT [6], [11]- [15].…”
Section: Introductionmentioning
confidence: 72%
“…Various significant factors contribute to explaining aggression, including social reputation [11], family dynamics and communication [12], [13], attitudes toward authority [14], psychological distress [15], and suicidal thoughts [16]. In the context of social relationships, it has been observed that when adolescents seek social recognition through transgressive behaviors, their likelihood of engaging in violent actions increases [17], [18]. In this regard, using RA can help aggressors maintain or enhance their status within the peer group [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, as a significant practical problem, most of the technologies considered in the current literature are newer and digital and have some inherent properties that make their implementation in an easy way difficult. Naturally, newer, unstable and opaque digital technologies present new challenges for teachers who are struggling to use more technology in their teaching to avoid misinformation or fake news [15], [16]. Teaching with technology is more complicated considering the new technological challenges present for teachers.…”
Section: Introductionmentioning
confidence: 99%